Diagnostic pitfalls of non-secretory myeloma: The biochemical perspective - Rashmi Rasi Datta; Ashutosh Awasthi (Journal of Clinical and Basic Research, 2024)
Background: Non-secretory multiple myeloma is a sporadic type of multiple myeloma with the proliferation of monoclonal plasmocytes in the bone marrow that cannot secrete or synthesize immunoglobulins. Its prevalence as a hematologic malignancy is low, and it is usually diagnosed by demonstration of monoclonal plasma cells ≥ 10% in the bone marrow with negative results on serum and urine electrophoresis and immunofixation studies. Methods: We present a case report where the patient's serum and whole blood samples were received in the study laboratory to evaluate the complete hemogram and metabolic profile. The metabolic and hematological profiles were deranged, subsequent to which the patient's clinical history was obtained from the treating clinician. It was discovered that the patient had presented with long-term weakness and back ache and was advised routine investigations along with magnetic resonance imaging (MRI) of the spine, which revealed the presence of osteolytic lesions. Following this, a gammopathy panel was requested. Results: Serum protein capillary electrophoresis and immunofixation electrophoresis revealed a normal pattern without any noticeable bands, distortions, or suspicious regions. However, the findings of the comprehensive gammopathy panel were suggestive of non-secretory multiple myeloma. Conclusion: In the absence of a detailed and meticulous work-up, a case of non-secretory multiple myeloma can be easily misdiagnosed. Here, we discuss the case in detail, the diagnostic pitfalls associated with it, and the role of serum free light chain assays in its diagnosis.